2019
DOI: 10.1371/journal.pone.0220035
|View full text |Cite
|
Sign up to set email alerts
|

The magnitude and factors associated with work-related back and lower extremity musculoskeletal disorders among barbers in Gondar town, northwest Ethiopia, 2017: A cross-sectional study

Abstract: Background Work-related back and lower extremity disorders often present remarkable health and economic burdens on societies. Occupational barbers are usually neglected in research and policy actions, mainly in developing countries, and are hence more vulnerable to the conditions. So far, information about the factors influencing back and lower extremity disorders among barbers in Ethiopia is unknown. Therefore, the aim of this study was to determine the prevalence and factors affecting back and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 37 publications
4
39
1
Order By: Relevance
“…Similarly, a study in Nigeria reported the prevalence of 76.3, 62.5, and 46.3% in low back, shoulder, and neck, respectively [4]. In our previous studies, we found 55.7% prevalence of back pain, 39.4% knee/ leg, 25.6% ankle [24], and 56.7% upper body [19].…”
Section: Introductionsupporting
confidence: 63%
“…Similarly, a study in Nigeria reported the prevalence of 76.3, 62.5, and 46.3% in low back, shoulder, and neck, respectively [4]. In our previous studies, we found 55.7% prevalence of back pain, 39.4% knee/ leg, 25.6% ankle [24], and 56.7% upper body [19].…”
Section: Introductionsupporting
confidence: 63%
“…Literature further reveals that hand/ wrist pain leads to a significant number of hairdressers visiting a doctor, and that shoulder and back pain contributes to sickness absences among hairdressers [13]. The high prevalence of CTS symptoms in this study, accompanied by the limited awareness of CTS, calls for efforts to improve the awareness of CTS among hairdressers in order to promote some behavioral changes as well as organizational and technological approaches [29,30]. In this study, it was also noted that the rent-a-chair facility makes every hairdresser their own employer.…”
Section: Study Limitationsmentioning
confidence: 89%
“…Further limitations of this study that need to be acknowledged are the possibility of recall bias and the self-reporting of CTS. It is not clear if the participants correctly remembered the presence of CTS symptoms in the past months There is convincing literature that hairdressers have more musculoskeletal disorders and higher associated pain intensity levels [15,29,30]. Literature further reveals that hand/ wrist pain leads to a significant number of hairdressers visiting a doctor, and that shoulder and back pain contributes to sickness absences among hairdressers [13].…”
Section: Study Limitationsmentioning
confidence: 99%
“…In this study, a total of 9,410 participants were included in 20 articles conducted in Ethiopia and published from 2017 to 2020 [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]: 9 (45.0%) articles [30,32,38,39,41,43,44,47,48] conducted in Oromia, three (15%) in Tigray [31,36,45], three (15%) in SNNP [29,34,35], three (15%) articles in Addis Ababa [33,40,46], two (10%) articles in Amhara regional state. All included studies were cross-sectional studies with a sample size ranging from 264 [45] to 771 [40] study participants.…”
Section: Characteristics Of Included Articlesmentioning
confidence: 99%
“…Among the included articles, 10(50%) [30,33,34,36,37,39,40,42,43,47] of the included articles were reported the prevalence of both low back pain and upper back pain, 9(45%) articles [29,31,32,35,41,[44][45][46]48] reported the prevalence of low back pain alone and 1(5%) [38] reported the prevalence of upper back pain alone. Furthermore, 8 (40%) included articles were published in 2020 [29,31,32,34,[44][45][46][47], followed by studies published in 2019 [36][37][38][41][42][43] that accounted 6(30%) of the included articles. Based on JBI Critical Appraisal tool [25], all of the included articles had a low risk of bias.…”
Section: Characteristics Of Included Articlesmentioning
confidence: 99%